Microwave mediated enhanced production of 5-hydroxymethylfurfural using choline chloride-based eutectic mixture as sustainable catalyst. (November 2021) - Mankar, Akshay R.; Pandey, Ashish; Modak, Arindam; Pant, K.K.
Abstract: The present work is a significant contribution to the production of 5-hydroxymethylfurfural (5-HMF) from carbohydrates-based feedstocks using environmentally benign choline chloride (ChCl)-based deep eutectic solvents (DESs) as catalyst in the presence of an inexpensive acetone/water solvent system. Under microwave irradiations, the acidity of organic acids in DESs can be a key criterion in screening out different eutectic mixtures. Among others, the ChCl: Lactic acid (LA) mixture was found to be the most efficient DES giving a 5-HMF yield of 30.12% on fructose dehydration. Optimization of different reaction parameters resulted in an enhanced 5-HMF yield of 87.2% in 30 min at 140 °C using ChCl: LA DES. The synergistic effect between LA and ChCl is also highlighted in boosting the 5-HMF yield. As compared to conventional oil bath heating, microwave heating resulted in significantly higher 5-HMF yield at a lower reaction time. The catalytic system ChCl: LA showed an appreciable yield of 5-HMF ranging from 83.1 to 71.2% for 5 recycle runs. Overall, we have developed a low cost, easy, energy-effective, green, and sustainable process ensuring high 5-HMF production. Graphical abstract: Image 1